Conidiobolomycosis: A case report of rare fungal infection from the eastern India - Somashree Dutta; Somenath Sarkar; Uttam Linka; Sujata Dora (Wolters Kluwer Medknow Publications, 2015)
Conidiobolomycosis is a rare chronic subcutaneous mycosis of nose and paranasal sinuse predominately affects the middle age men in tropical countries. It is caused by a saprophytic fungus "Conodiobolus coronatus", which can survives in soils and dried vegetables for long period of time. C. coronatus belongs to the class Zygomycetes, order Entomophthorales. It is a fungus composed of thick- walled, short hyphae that grows at temperatures of 30 to 37 degrees C. Here we report a case of conidiobolomycosis in a 55- year- old farmer presented with a subcutaneous swelling over the left side of nose extending to left cheek.